Learning Strategies in the Era of Society 5.0 in Overcoming Students' Social Inequality - Andriani Andriani; Ali Hanafi; Harifuddin Harifuddin (International Journal on Advanced Science, Education, and Religion, 2026)
This research is motivated by the emergence of social gaps in students' learning in the Society 5.0 era, characterized by differences in access to technology, quality of learning experiences, social participation, and opportunities for self-development at SMPN 7, Sinjai Regency. This study aims to analyze teacher learning strategies, forms of social gaps in students, as well as supporting and inhibiting factors in overcoming these gaps. This research uses a qualitative approach with a case study type, which was conducted at SMPN 7, Sinjai Regency. Data collection techniques were carried out through in-depth interviews, observation, and documentation with key informants students and key informants teachers. The results show that the learning strategies implemented by teachers include differentiated learning, the use of learning technology, collaborative learning through heterogeneous groups, and providing motivation and appreciation to students. Forms of social gaps in students include gaps in access to learning, gaps in the quality of learning experiences, gaps in social participation in the classroom, and gaps in opportunities for self-development. Meanwhile, supporting factors include the availability of school technology facilities and teachers' digital competence, while inhibiting factors include differences in students' economic backgrounds and variations in students' learning motivation and digital readiness. The conclusion of this study shows that effective learning strategies must be supported by equal distribution of facilities, increased teacher competency, and an adaptive pedagogical approach to create inclusive and socially just learning.